Assessing chromate reduction by dissimilatory iron reducing bacteria using mathematical modeling. (November 2015) - Peng, Lai; Liu, Yiwen; Gao, Shu-Hong; Dai, Xiaohu; Ni, Bing-Jie
Highlights: Three models were proposed to evaluate Cr (VI) reduction by IRB. Two-pathway rather single-pathway model could describe the experimental data. Both chemical and microbial pathways contributed to Cr reduction by IRB. The electron donor availability and HRT regulated the abiotic and microbial pathways. Abstract: Chromate (Cr (VI)) is a ubiquitous contaminant in aquifers and soils, which can be reduced to its trivalent counterpart (Cr (III)), with the hazard being relieved. The coupling microbial and chemical reduction by dissimilatory iron reducing bacteria (IRB) is a promising approach for the reduction of Cr (VI) to Cr (III). In this work, three mathematical models with different Cr (VI) reduction pathways were proposed and compared based on their ability to predict the performance of an IRB-based stirred-flow reactor treating Cr (VI) contaminated medium and to provide insights into the possible chemical or microbial pathways for Cr (VI) reduction in the system. The Cr (VI) reduction was considered as chemical reaction between Fe (II) and Cr (VI), direct microbial reduction by IRB and combined biotic–abiotic reduction in these three models, respectively. Model evaluation results indicated that the model incorporating both chemical and microbial Cr (VI) reductions could well describe the system performance. In contrast, the other two single-pathway models were not capable of predicting the experimental data, suggesting that both chemical and microbial pathways contributed to Cr (VI) reduction by IRB. The validity of the two-pathway model was further confirmed by an independent experimental data set with different conditions. The results further revealed that the organic carbon availability and Cr (VI) loading rates for the IRB in the system determined the relative contributions of chemical and microbial pathways to overall Cr (VI) reduction.